Books Reviewed Elsewhere - Douglas, John (Academy of Management Review, 1977)
The article presents a list of books review in other publications including, “Dilemmas of Administrative Behavior. Personnel Psychology,” Vol. 29, by J. D. Aram, “Sociology of Organizations. Personnel Management,” Vol. 8, by A. M. Bowey and “Developing Tomorrow's Managers Today. Personnel Psychology,” Vol.29, by F. W. Dinsmore.